Involvement of brain-derived neurotrophic factor signaling in the pathogenesis of stress-related brain diseases - Tadahiro Numakawa; Ryutaro Kajihara; Ryutaro Kajihara (Frontiers in Molecular Neuroscience, 2023)
Neurotrophins including brain-derived neurotrophic factor, BDNF, have critical roles in neuronal differentiation, cell survival, and synaptic function in the peripheral and central nervous system. It is well known that a variety of intracellular signaling stimulated by TrkB, a high-affinity receptor for BDNF, is involved in the physiological and pathological neuronal aspects via affecting cell viability, synaptic function, neurogenesis, and cognitive function. As expected, an alteration of the BDNF/TrkB system is suspected to be one of the molecular mechanisms underlying cognitive decline in cognitive diseases and mental disorders. Recent evidence has also highlighted a possible link between the alteration of TrkB signaling and chronic stress. Furthermore, it has been demonstrated that downregulation of the BDNF/TrkB system and chronic stress have a role in the pathogenesis of Alzheimer’s disease (AD) and mental disorders. In this review, we introduce current evidence showing a close relationship between the BDNF/TrkB system and the development of cognition impairment in stress-related disorders, and the possible contribution of the upregulation of the BDNF/TrkB system in a therapeutic approach against these brain diseases.